2015
DOI: 10.1093/eurheartj/ehv653
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol crystal induced arterial inflammation and destabilization of atherosclerotic plaque

Abstract: Evolution of plaque that is prone to rupture is characterized by inflammation and physical changes. Accumulation of low-density lipoprotein in the sub-intima provides esterified cholesterol (ESC) to macrophages and smooth muscle cells that convert it into free cholesterol (FRC) by cholesteryl ester hydrolases (CEHs). Membrane-bound cholesterol carriers transport FRC to high-density lipoprotein (HDL). Impaired HDL transport function and altered composition can lead to extracellular accumulation of FRC, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(128 citation statements)
references
References 55 publications
2
125
0
1
Order By: Relevance
“…19 We could detect a significant increase of the complex CHIP/ILK in SP-NO-treated MAEC ( Figure IIIB in the online-only Data Supplement). Next, we measured ILK levels in MAEC transfected with CHIP small interfering RNA or scrambled small interfering RNA as control.…”
Section: No Induces Ilk Ubiquitination and Leads To Ilk Degradation Imentioning
confidence: 87%
See 1 more Smart Citation
“…19 We could detect a significant increase of the complex CHIP/ILK in SP-NO-treated MAEC ( Figure IIIB in the online-only Data Supplement). Next, we measured ILK levels in MAEC transfected with CHIP small interfering RNA or scrambled small interfering RNA as control.…”
Section: No Induces Ilk Ubiquitination and Leads To Ilk Degradation Imentioning
confidence: 87%
“…19 To test whether inflammation may regulate endothelial ILK expression, we followed the levels of ILK in response to the proinflammatory cytokine TNF-α (tumor necrosis factor α), which induces several proinflammatory genes, including iNOS, in endothelial cells. In mouse aortic endothelial cell (MAEC) stimulated for 24 hours with 100 ng/mL TNF-α, a significant increase of iNOS was detected, together with reduced ILK levels ( Figure 2A, top), whereas pharmacological inhibition of iNOS activity with 1400W prevented ILK decreased expression in TNF-α-stimulated MAEC.…”
Section: Inos-derived No Reduces Ilk Content In Endothelial Cells By mentioning
confidence: 99%
“…Our study confirmed this hypothesis by identifying an association between cholesterol crystals in embolic debris and new DWI lesions after CAS. It is known that LDL oxidation leads to endothelial dysfunction and induces the expression of various proinflammatory cytokines, chemokines, and adhesion molecules [7]. Moreover, macrophages are activated by oxidized LDL, whereby they release cytokines to promote further macrophage recruitment and metalloproteinase secretion [23].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol crystals generated by low-density lipoprotein (LDL) in the plaque can initiate inflammation and are associated with positive remodeling of the arterial wall and destabilization of the plaque [7,8]. A study on small sample analyzed aspirated blood from CAS procedures performed with distal balloon protection and suggested a possible association between cholesterol crystals and distal embolism in CAS [4].…”
Section: Introductionmentioning
confidence: 99%
“…TCFA are also rich in macrophages, which can lead to plaque destabilization by secreting matrix metalloproteinases that readily degrade collagen and thin the fibrous cap leading to plaque rupture [11,12]. TCFA also contain cholesterol crystals that can penetrate and disrupt the fibrous cap and can promote the secretion of pro-inflammatory cytokines resulting in the activation of the immune system [14,15]. Other plaque features associated with increased vulnerability are intra-plaque hemorrhages and microcalcifications [12,16].…”
Section: Introductionmentioning
confidence: 99%